Relevance of uncertainty on the volatility and trading volume in the US Treasury bond futures market - Helinä Laakkonen (Bank of Finland, 2015)
This paper studies the impact of uncertainty on the investors' reactions to news on macroeconomic statistics. With daily data on realized volatility and trading volume, we show that the investors in the US Treasury bond futures market react significantly stronger to US macroeconomic news in times of low macroeconomic, financial and political uncertainty. We also find that investors are more sensitive to the uncertainty in the financial market compared to the macroeconomic and political uncertainties. Our results might partly explain the sudden freeze and low liquidity in some financial markets during the latest financial crisis.
URN:NBN:fi:bof-201503021055
Keywords: G12; G14; C22; 330